Catoe Rimueng: Upaya Meningkatkan Kepercayaan Diri Anak dan Remaja melalui Seni Bertutur di Panti Asuhan Media Kasih - Rizki, Aulia Maulana; Zulfikri; Prawita, Tiwidian; Naufal, Muhammad Alif (Devotion : Jurnal Pengabdian Psikologi, 2023)
Self confidence is considered very important for the development of adolescents and children’s as it is one of the standard criteria for achiving individual social and emotional development. Adolescents and children’s who possess self-confidence will have a positive self-image and self-concept. On the other hand, adolescents and children with low self confidence will show doubtful behavior when completing tasks, do not dare to speak in a group activities without support, tend to withdraw and avoid participating in discussion, isolate themselves from their environment, and tend to be aggressive. Through catoe rimueng training and the art of speech activities, children’s in orphanage can enhance their self confidence. The objective of this community service is to boost the self confidence of the children at Media Kasih Orphanage in Banda Aceh City. The observation instrument used before and after the implementation of this community service is The Lautser Self Confidence Scale (2012). Based on the observation, there is an increase in children’s self confidence before and after the implementation. Thus, there is potential for program sustainability with defined product prototypes.